2021
DOI: 10.1002/ptr.7267
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin combined with low‐dose paclitaxel synergistically inhibits epithelial–mesenchymal transition and induces cell apoptosis on esophageal carcinoma in vitro and in vivo

Abstract: Although paclitaxel is a promising frontline chemotherapy agent for various malignancies, the clinical applications have been restricted by side effects, drug resistance, and cancer metastasis. The combination of paclitaxel and other agents could be the promising strategies against malignant tumor, which enhances the antitumor effect through synergistic effects, reduces required drug concentrations, and also suppresses tumorigenesis in multiple ways. In this study, we found that luteolin, a natural flavonoid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…87 Luteolin suppresses cell cycle progression, growth, survival, EMT, migration, and chemoresistance by the modulation of cyclin, survivin, Myc, p21, p53, poly (adenosine diphosphate [ADP]-ribose) polymerase (PARP), Bim, caspase, SIRT1, c-Jun N-terminal kinase (JNK), and ROS signaling. 88 Quercetin targets cyclin, DNA methyltransferase 1, histone deacetylase 1, caspase, p16, NF-kappa B, growth arrest and DNA damage-inducible protein (GADD)-β, p53-inducible gene 3, p18, E-cadherin, VEGF-A, matrix metalloproteinase (MMP), miR-1-3p/ transgelin-2, and phosphatase and tensin homolog (PTEN) pathways 89 ; these effects result in the suppression of drug resistance, growth, proliferation, invasion, angiogenesis, and cancer stemness of EC cells. 89 The anticancer properties of FDY003 against diverse kinds of cancer cells have been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…87 Luteolin suppresses cell cycle progression, growth, survival, EMT, migration, and chemoresistance by the modulation of cyclin, survivin, Myc, p21, p53, poly (adenosine diphosphate [ADP]-ribose) polymerase (PARP), Bim, caspase, SIRT1, c-Jun N-terminal kinase (JNK), and ROS signaling. 88 Quercetin targets cyclin, DNA methyltransferase 1, histone deacetylase 1, caspase, p16, NF-kappa B, growth arrest and DNA damage-inducible protein (GADD)-β, p53-inducible gene 3, p18, E-cadherin, VEGF-A, matrix metalloproteinase (MMP), miR-1-3p/ transgelin-2, and phosphatase and tensin homolog (PTEN) pathways 89 ; these effects result in the suppression of drug resistance, growth, proliferation, invasion, angiogenesis, and cancer stemness of EC cells. 89 The anticancer properties of FDY003 against diverse kinds of cancer cells have been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that resveratrol, a powerful alternative to antioxidants, inhibits a variety of cancers ( Rauf et al, 2018 ). Luteolin inhibits paclitaxel resistance in esophageal cancer and synergistically inhibits the EMT process in combination with low-dose paclitaxel, thereby inducing apoptosis in esophageal cancer in vitro and in vivo ( Zhao Y et al, 2021 ; Qin et al, 2021 ). In addition, apigenin, icaritin, oridonin, berberine and curcumin have all been shown to have anti-esophageal cancer efficacy ( Jiang et al, 2017 ; Han et al, 2018 ; Jiang et al, 2019 ; Kwiecien et al, 2019 ; Qiu et al, 2019 ).…”
Section: Epigenetics In the Treatment Of Esophageal Cancermentioning
confidence: 99%
“…The tumorigenicity of paclitacel-resistant oesophageal cancer cells was also inhibited by luteolin and this effect was achieved without significant in vivo damage [ 107 ]. Furthermore, as Qin et al study, luteolin could have substantial potency in clinical application and was presented as a new chemosensitizer agent in the treatment of esophageal cancer [ 108 ]. Using a low dose of paclitaxel with luteolin was shown to have synergistic effects on the regulation of esophageal cancer cell migration, proliferation, EMT, and apoptosis [ 108 ].…”
Section: Luteolin (3’ 4’ 5 7-tetrahydroxyflavone)mentioning
confidence: 99%